Pengaruh Pertumbuhan Penjualan dan Likuiditas terhadap Perubahan Laba dengan Kinerja Keuangan sebagai Variabel Mediasi pada Perusahaan Manufaktur Subsektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2022–2024 - Fahrezi, Ricard Ryan; Nadhiroh, Umi; Wardhani, Rike Kusuma; Al-Gifari, Annas AQ (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to examine the effect of sales growth and liquidity on earnings changes with financial performance as a mediating variable in manufacturing companies in the food and beverage subsector listed on the indonesia stock exchange (IDX) during the 2022–2024 period. The variables employed in this study include sales growth, liquidity proxied by the current ratio, financial performance proxied by return on assets, and earnings changes. This research adopts a quantitative approach using panel data regression analysis and mediation analysis through the sobel test. The analysis is conducted using two structural equations. The first structural equation employs the random effect model, while the second structural equation applies the common effect model, based on the results of model selection tests. The findings indicate that sales growth has a negative and significant effect on earnings changes. Liquidity, as measured by the current ratio, has a positive but insignificant effect on earnings changes. Similarly, financial performance, proxied by return on assets, has a positive but insignificant effect on earnings changes. Furthermore, financial performance is unable to mediate the effect of sales growth on earnings changes and is also unable to mediate the effect of liquidity on earnings changes.